2000
DOI: 10.1046/j.1365-2133.2000.03674.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic spongiosis in association with bullous pemphigoid and chronic lymphocytic leukaemia

Abstract: We report the onset of an unusual blistering eruption following a diagnosis of B-cell chronic lymphocytic leukaemia (CLL). The histology consistently showed eosinophilic spongiosis, but the diagnosis of bullous pemphigoid was only confirmed after 13 years by repeated immunofluorescence studies. The occurrence of subepidermal blistering diseases in association with B-cell lymphoproliferative disorders is rare; a recent study showed that the majority of these cases are epidermolysis bullosa acquisita, confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In five cases, BP was diagnosed simultaneously with cancer, while in the other two cases (both CLL) skin eruptions arose subsequent to the diagnosis of malignancy. In five cases, remission of BP was obtained only after the achievement of remission of the hematological disorder .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In five cases, BP was diagnosed simultaneously with cancer, while in the other two cases (both CLL) skin eruptions arose subsequent to the diagnosis of malignancy. In five cases, remission of BP was obtained only after the achievement of remission of the hematological disorder .…”
Section: Discussionmentioning
confidence: 99%
“…In five cases, BP was diagnosed simultaneously with cancer, while in the other two cases (both CLL) skin eruptions arose subsequent to the diagnosis of malignancy. In five cases, remission of BP was obtained only after the achievement of remission of the hematological disorder . A BP associated with myelodysplastic syndrome was found to be recalcitrant to the therapy; it initially responded to high doses of prednisolone and azathioprine, but a worsening and a lack of therapeutic response of the bullous eruption was observed, following the progression of the underlying hematological disease for which there was no treatment …”
Section: Discussionmentioning
confidence: 99%
“…This finding implies a link between the antigen-presenting capabilities of LC, T cell activation, and subsequent B cell stimulation in the pathogenesis of this antibody-mediated disease. Like others [3], when reporting routine biopsies, we occasionally encounter small collections of LC within the epidermis in a variety of dermatoses. These bgranuloma-likeQ aggregates appear to form as a result of proinflammatory cytokines that recruit LC to the skin [4].…”
Section: Langerhans Cell Component In Bullous Pemphigoid-like Lesionsmentioning
confidence: 84%
“…Nevertheless, it has been shown that, at least in patients in whom circulating anti-230-kd autoantibody is detected in the serum, the antibody is not synthesized by the leukemic cells [2] and that it is more related to the polyclonal hypergammaglobulinemia that can be found in some of these patients [3].…”
Section: Langerhans Cell Component In Bullous Pemphigoid-like Lesionsmentioning
confidence: 99%
“…EAC has been associated with drugs and a wide variety of disorders including infections, endocrine and immunological disorders, haematological and other neoplastic disorders 1 . Annular erythemas have been described as the clinical presentation of bullous pemphigoid 7 and hypereosinophilic dermatitis 8 in two patients with CLL but, to the best of our knowledge, EAC per se has not been described in association with CLL. Although this association may be coincidental, the close temporal association prompts us to speculate that EAC in this case was a nonspecific manifestation of CLL.…”
mentioning
confidence: 99%